Growth promotion and stress tolerance of soybean plants driven by seed treatment with synthetic bacterial community of soybean-associated beneficial bacteria - Calderon, Rosalie B.; Gouli, Sandeep; Barphagha, Inderjit; Ham, Jong Hyun (Frontiers in Plant Science, 2026)
IntroductionBeneficial microbes provide a sustainable approach to improving crop production and reducing risks from intensive farming. Microbial consortia, complementary traits, often outperform single strains in promoting plant health. This study aimed to develop an effective biological strategy to enhance soybean growth and health using beneficial bacterial consortia.MethodsBacteria were isolated from the root endosphere and rhizosphere of field-grown soybean plants and screened for traits such as nutrient solubilization, hormone production, and pathogen suppression. Seven synthetic bacterial communities (SBCs), each comprising 5 to 20 SABB strains, were constructed to evaluate their potential in promoting soybean growth and health. Impact of SBC seed treatments on the structure of soybean microbiota was also investigated.ResultsTwo SBC sets, Set2 and Setm4, demonstrated superior performances in enhancing plant growth and resistance to the fungal pathogen Rhizoctonia solani when applied via seed treatment. Notably, seed treatment with Set2 or Setm4 also improved soybean resilience to abiotic stresses, including drought and waterlogging. Profiling of the root endosphere and rhizosphere microbiota revealed that SBC application through seed treatment significantly altered the composition of soybean-associated microbial community, including the enrichment of key symbiotic taxa, such as Bradyrhizobium elkanii, and increased microbial network complexity.DiscussionThe beneficial effects of SBC through seed treatment are closely related to microbiome restructuring in soybean roots. This study provides valuable insights into the development of innovative and sustainable crop management strategies, highlighting the potential of SBC-based seed treatments to enhance growth and stress resilience in soybeans and other major crops.